REFORMS FOR THE DEVELOPMENT OF WOMEN’S ENTREPRENEURSHIP IN UZBEKISTAN - Usmonova, Mokhigul (Educational Research in Universal Sciences, 2023)
In this article, the role of women in social life, measures to improve living conditions, expand the opportunities for women entrepreneurs, ensure gender equality, creating the necessary conditions and opportunities for women, their place in society, and their position in the field of entrepreneurship was analyzed based on available sources.